Ecobrick as a Sustainable Lifestyle Implementation in Shaping Students’ Creativity and Environmental Care - Zulfa, Athena; Indasari, Nur Laili; Ummah, Fadhilatul (EDUCARE: Journal of Primary Education Published by Faculty of Tarbiyah and Teacher Training, Kiai Haji Achmad Siddiq State Islamic University of Jember, East Java, Indonesia, 2025)
The low levels of creativity and environmental care among elementary school students are the main issues addressed in this study. Implementing a sustainable lifestyle through the Pancasila Student Profile Strengthening Project (P5) is necessary to overcome these challenges. This research focuses on exploring Ecobrick activities within the P5 project as an effort to effectively and sustainably foster students' creativity and environmental awareness. The study employs a descriptive qualitative approach using instruments such as closed questionnaires, interviews, observations, and documentation to analyze the implementation of Ecobrick activities in enhancing the creativity and environmental care of elementary school students. Data collection, reduction, presentation, and conclusion drawing were used in the analysis process. The results of this research show that the implementation of the Pancasila Student Profile Strengthening Project (P5) with the theme of sustainable lifestyle through Ecobrick activities is effective in enhancing elementary school students' creativity. The findings indicate that Ecobrick activities successfully met all student creativity indicators, such as curiosity, questioning skills, generating creative ideas, and independent learning, while also increasing students’ environmental awareness. This research contributes empirical evidence regarding the effectiveness of the P5 project themed on sustainable lifestyle through Ecobrick activities in fostering students' creativity and environmental care. It strengthens theoretical understanding of the benefits of project-based learning in developing student creativity and provides practical guidance for teachers and schools to implement similar activities as part of a curriculum integrated with Pancasila values.